INKUBATOR PEMELIHARAAN ANAK AYAM MENGGUNAKAN SENSOR SUHU DAN TENAGA SURYA BERBASIS IOT - Yunita Indah Sari; Kurnia Paranita Kartika Riyanti; Zunita Wulansari (LPPM Politeknik Jambi, 2021)
The development of free-range chickens has several obstacles, including low productivity, small scale, the way to overcome the limitations of free-range chickens is to apply a separate breeding process from the parent by means of an incubator. The goal in the incubator is to produce more chicks. This study aims to provide convenience for farmers. Because this automation tool can make it easier for farmers to maintain and care for chicks, because basically chick incubators do require special maintenance and the use of IoT in the electronics world has been very much and is still growing. The use of IoT has penetrated almost all human activities such as livestock, agriculture, fisheries and various household appliances. The function of IoT itself in these fields is to simplify human work, monitor various equipment remotely and increase the effectiveness of the tool. So the pins took the title Chicken Care Incubator Using Temperature Sensors And Solar Power Based On Iot using NodeMCU microcontrollers, temperature sensors, voltage sensors, batteries, solar panels, relays, lights. The method used for research is Research and Development (R&D). The researcher used the XAMPP application and opened a web page to find out the system in the chick rearing incubator automatically values ​​the battery voltage, temperature, lights on and off and time. The results of the design of the chick rearing incubator are automatically successful with a percentage of 100%. The results of the validator test are 87.5% and chicken breeders are 96.25%.